Icariin improves testicular dysfunction via enhancing proliferation and inhibiting mitochondria-dependent apoptosis pathway in high-fat diet and streptozotocin-induced diabetic rats - He, Weiguo; Liu, Huiqing; Hu, Linlin; Wang, Yaohui; Huang, Lane; Liang, Aihong; Wang, Xuan; Zhang, Qing; Chen, Yi; Cao, Yi; Li, Suyun; Wang, Junli; et al. (Reproductive biology and endocrinology, 2021)
Background Diabetes mellitus (DM), a chronic metabolic disease, severely impairs male reproductive function. However, the underpinning mechanisms are still incompletely defined, and there are no effective strategies or medicines for these reproductive lesions. Icariin (ICA), the main active component extracted from Herba epimedii , is a flavonoid traditionally used to treat testicular dysfunction. Whether ICA can improve male reproductive dysfunction caused by DM and its underlying mechanisms are still unclear. In this study, by employing metformin as a comparative group, we evaluated the protective effects of ICA on male reproductive damages caused by DM and explored the possible mechanisms. Methods Rats were fed with a high fat diet (HFD) and then intraperitoneally injected with streptozotocin (STZ) to induce diabetes. Diabetic rats were randomly divided into T2DM + saline group, T2DM + metformin group and T2DM + ICA group. Rats without the treatment of HFD and STZ were used as control group. The morphology of testicular tissues was examined by histological staining. The mRNA expression levels were determined by quantitative real-time PCR. Immunostaining detected the protein levels of proliferating cell nuclear antigen (PCNA), hypoxia-inducible factor 1-alpha (HIF-1α) and sirtuin 1 (SIRT1) in testicular tissues. TUNEL assay was performed to determine cell apoptosis in the testicular tissues. The protein expression levels of HIF-1α and SIRT1 in the testicular tissues were determined by western blot assay. Results ICA effectively improved male reproductive dysfunction of diabetic rats. ICA administration significantly decreased fasting blood glucose (FBG) and insulin resistance index (IRI). In addition, ICA increased testis weight, epididymis weight, sperm number, sperm motility and the cross-sectional area of seminiferous tubule. ICA recovered the number of spermatogonia, primary spermatocytes and Sertoli cells. Furthermore, ICA upregulated the expression of PCNA, activated SRIT1-HIF-1α signaling pathway, and inhibited intrinsic mitochondria dependent apoptosis pathway by upregulating the expression of Bcl-2 and downregulating the expression of Bax and caspase 3 . Conclusion These results suggest that ICA could attenuate male reproductive dysfunction of diabetic rats possibly via increasing cell proliferation and decreasing cell apoptosis of testis. ICA potentially represents a novel therapeutic strategy against DM-induced testicular damages.